The relationship between the influence of social media and the demand for aesthetic dental procedures: A literature review (Research, Society and Development, 2026)
This study aimed to analyze the relationship between virtual networks and the demand for aesthetic procedures in Dentistry, focusing on identifying their potential risks and implications. This is an integrative systematic review of the literature, conducted through searches in the scientific databases PubMed and Web of Science. Studies addressing social media, marketing in aesthetic dentistry, professional ethics, and overtreatment were included, followed by critical reading and categorization of findings according to the proposed objectives. The results showed that social media and marketing strategies influence the construction of idealized aesthetic standards, impacting individuals’ self-perception and increasing the demand for aesthetic procedures. It was also observed that the commercialization of dentistry may weaken professionalism and trust in the dentist–patient relationship. Furthermore, the overexposure of clinical cases contributes to the creation of perceived needs and overtreatment. It is concluded that virtual mechanisms play a significant role in shaping aesthetic standards and intensifying the demand for interventions, affecting professional practice and favoring ethically questionable behaviors, highlighting the need for regulation and the strengthening of ethics in dentistry.